Mindfulness for children in public schools: Current research and developmental issues to consider. Issue 2 (2nd April 2016) - Chadwick, Jeanne; Gelbar, Nicholas W.
Abstract : Mindfulness-based interventions have increased in popularity over the past decade and interest continues to increase in the potential to use mindfulness-based interventions in schools. The current research concerning school-based mindfulness-based interventions is reviewed in this article. This research base is fragmented, as most of the studies are underpowered, use uneven dosing, and have not considered important developmental covariates such as cognitive ability. Suggestions for future research are offered including larger, more systematic intervention studies. Practical considerations for providing mindfulness-based interventions in schools are offered, including potential program evaluation outcome measures.